47.0k views
1 vote
Please answer the 16th qs

Please answer the 16th qs-example-1

1 Answer

5 votes

Answer:

p = 13

Explanation:

When a polynomial f(x) is divided by (x + h) then the remainder is f(- h)

Here both polynomials are divided by (x + 1)

Evaluate them both for x = - 1

3(- 1)³ - 5(- 1)² - 4(- 1) + p, that is

- 3 - 5 + 4 + p

= p - 4 → A

6(- 1)³ + p(- 1)² + 9(- 1) + 5, that is

- 6 + p - 9 + 5

= p - 10 → B

Given that A = 3B, then

p - 4 = 3(p - 10)

p - 4 = 3p - 30 ( subtract 3p from both sides )

- 2p - 4 = - 30 ( add 4 to both sides )

- 2p = - 26 ( divide both sides by - 2 )

p = 13

User MietieMn
by
5.2k points